Do private health providers adhere to National Tuberculosis Guideline while assigning treatment outcome? Findings from a lower middle-income country - Adepoju, Victor Abiola; Adejumo, Olusola Adedeji; Adepoju, Oluwatoyin Elizabeth; Adeniyi, Marius Olusola; Etuk, Victoria; Nzekwe, Iheoma; Inegbeboh, Jude O.; Adelekan, Ademola; Oladimeji, Olanrewaju (Frontiers in Public Health, 2022)
Background Treatment success rate is an important indicator to measure the performance of National Tuberculosis Program (NTP). There are concerns about the quality of outcome data from private facilities engaged by NTP. Adherence of private providers of tuberculosis care to NTP guideline while assigning treatment outcomes to patients is rarely investigated. We aimed to determine whether Lagos private facilities adhere to domestic TB guideline while assigning treatment outcome and the availability of periodic sputum acid fast bacilli (AFB) results. Method A retrospective review of facility treatment register and treatment cards of TB patients managed between January-December 2016 across 10 private DOTS facilities involved in the Public Private Mix (PPM) in Lagos, Nigeria. The study took place between January-June 2019. Results Of the 1,566 patients, majority (60.7%) were male, >30 years (50.2%), HIV negative (88.4%) and attended private-not-for-profit (78.5%). Reported treatment success rate (TSR) was 84.2% while the actual TSR was 53.8%. 91.1%, 77.6% and 70.3% of patients had sputum AFB at 2/3, month 5 and month 6 while 68.6% had all the 3 sputum AFB in the register. Healthcare workers (HCWs) were adherent in assigning treatment outcome for 65.6% of TB patients while 34.4% of patients were assigned incorrect treatment outcome. Most variations between reported and actual treatment outcomes were with cured (17%) and completed (13.4%). Successful outcome and unsuccessful outcome were over-reported by 30.4% and 4.1% respectively .